Transkripsi Musik Gong Timor Menggunakan Continous Wavelet Transform (CWT) - Yovinia C H Siki; Yoyon K Suprapto (Department of Mechanical Engineering, University of Udayana, 2016)
Abstrak:Transkripsi musik gong timor dibutuhkan untuk pengembangan aplikasi pengolahan sinyal musik seperti mengeditmusik, melacak tempo musik dan analisis sinyal musik lainnya yang dapat membantu para pemain pemula untukbelajar bagaimana memainkan alat musik gong. Rumitnya analisa suara musik gong dibandingkan analisa peralatanmusik barat karena dipengaruhi oleh cara pembuatan peralatan yang kurang sempurna, dan cara pemukulan peralatanyang berdasar kira-kira. Dengan menggunakan metode CWT, sinyal music gong dikonvolusi untuk menghasilkanscalogram music gong domain skala dan frekuensi. Estimasi nada gong diperoleh menggunakan sebuah proses notegenerating. Keberhasilan transkripsi ditentukan dengan menghitung error yaitu ketepatan menterjemah. Dimana adanada yang seharusnya tidak ada tetapi dikenali sebagai note (insertion), ada nada yang tidak dikenali sehinggaterhapus (deletion) dan ada nada yang dikenali salah (substitution).Kata kunci: Gong timor, transkripsi musik, CWT, scalogram, note generatingAbstract:Gong timor music transcription used to develop some other aplication in music signal processing such as music editing,beat detection, etc. With this transcription, new percussionist of gong can learn more easily to playing gong instrument.Analyzing music gong are more difficult than any other music instrument, it is because gong instrument created withvery simple tools and the percussionist playing this instrument by feelings of any other instrument in gamelan. Musicgong signal convoluted using CWT to create scalogram of music gong in scale and frequency domain. Tone estimationobtained using a note generating process. The success of transcription process determined by calculating errors intranscription results. Which are sometimes there is a tone that shouldn’t exist but marked as a tone (insertion), or thereis a tone but the transcription process doesn’t recognize it (deletion) and sometimes there is a tone but marked as adifferent tone (substitution).Keywords: Gong timor, music transcription, CWT, scalogram, note generating